Behavioral assessment of a trichotillomania case in a teenage girl (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
The purpose of this study was to conduct a behavioral assessment with a teenage girl with trichotillomania, which consist of pulling out one’s hair. A teenage girl and her mother participated in the study. The caregiver filled the following instruments and scales: structured interview for parents and caregivers, Child Behavior Checklist for ages 6 to 18 (CBCL/ 6-18), and Parental Style Inventory (IEP). The teenager filled the following instruments and scales: structured interview for teenagers, Youth Self Report for ages 11 to 18 (YSR), and Social Skills Inventory for Adolescents (IHSA). Results showed that trichotillomania behavior produces positive reinforced and punitive consequences; the teenager presented deficits in her social repertoire, affective problems, anxiety, and problems related to obsessive-compulsive disorder. The study suggests the conduction of new studies on the relationship between parental practices and trichotillomania.
Keywords: trichotillomania; behavioral assessment; social skills; parental practices